2007
DOI: 10.5194/cp-3-77-2007
|View full text |Cite
|
Sign up to set email alerts
|

Linking glacial and future climates through an ensemble of GCM simulations

Abstract: Abstract. In this paper we explore the relationships between the modelled climate of the Last Glacial Maximum (LGM) and that for doubled atmospheric carbon dioxide compared to the pre-industrial climate by analysing the output from an ensemble of runs from the MIROC3.2 GCM.Our results lend support to the idea in other recent work that the Antarctic is a useful place to look for historical data which can be used to validate models used for climate forecasting of future greenhouse gas induced climate changes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 20 publications
8
90
0
Order By: Relevance
“…In these SH latitudes, the reduction of the atmospheric heat gain is as large as the surface cooling, which suggests that CO 2 and water vapour contribute most to the cooling. This is consistent with several studies suggesting that the polar amplification over Antarctica may provide useful evidence on climate sensitivity (Manabe and Broccoli, 1985;Masson-Delmotte et al, 2006), although the relationship is complex Hargreaves et al, 2007).…”
Section: Results For the Last Glacial Maximumsupporting
confidence: 78%
“…In these SH latitudes, the reduction of the atmospheric heat gain is as large as the surface cooling, which suggests that CO 2 and water vapour contribute most to the cooling. This is consistent with several studies suggesting that the polar amplification over Antarctica may provide useful evidence on climate sensitivity (Manabe and Broccoli, 1985;Masson-Delmotte et al, 2006), although the relationship is complex Hargreaves et al, 2007).…”
Section: Results For the Last Glacial Maximumsupporting
confidence: 78%
“…It was found that the strength of some of the fast feedbacks depends on the background climate state. This is in agreement with other model-based approaches, which proposed a state dependency of water vapour (Meraner et al, 2013) or clouds (Crucifix, 2006;Hargreaves et al, 2007). Distinguishing different climate regimes in palaeodata covering the last 800 000 years (0.8 Myr), the time for which ice core records exist, von der Heydt et al (2014) revealed a ∼ 36 % larger S [CO 2 ,LI] for "warm" background climates when compared to "cold" climates.…”
supporting
confidence: 81%
“…Crucifix, 2006;Hargreaves et al, 2007;Yoshimori et al, 2011;Yin and Berger, 2012;Caballero and Huber, 2013;Goldner et al, 2013;Kutzbach et al, 2013;Meraner et al, 2013) and palaeodata-based (PALAEOSENS-Project Members, 2012;von der Heydt et al, 2014) approaches have already indicated that S varies for different background climates; see also a recent review of Knutti and Rugenstein (2015) on the limits of linear models to constrain climate sensitivity. The majority of simulation studies shows a rise in climate sensitivity for a warmer background climate.…”
mentioning
confidence: 99%
“…Masson-Delomtte et al, 2006;Kageyama et al, 2006;Braconnot et al , 2007;Hargreaves et al, 2007;Roche et al, 2007;Weber et al, 2007). The objective of this study is to investigate the surface climate and atmospheric field over East Asia and the North Pacific during the LGM by comparing the results obtained using the different CGCMs in the PMIP2 database and the paleoclimatic reconstructions.…”
mentioning
confidence: 99%